Douglas-fir beetle (Coleoptera: Curculionidae) response to single-point-source 3-methylcyclohex-2-en-1-one (MCH) releasers. Issue 2 (18th April 2021) - Ross, Darrell W.; Sullivan, Brian T.
Abstract: The Douglas-fir beetle ( Dendroctonus pseudotsugae Hopkins) (Coleoptera: Curculionidae) antiaggregation pheromone, 3-methylcyclohex-2-en-1-one (MCH), has been used since 2000 to protect high-value trees and stands throughout western North America. Operational treatments involve placing individual releasers on a 12 m × 12 m grid throughout the area to be protected. In this study, six widely spaced trap lines were established with aggregation attractant–baited traps located 1, 3, 9, 27, and 81 m from a location where an operational MCH release device was alternately either present or absent, and changes in catches caused by the MCH device were assessed at all distances. Trap catches were suppressed by about 70% at one and three metres, by 50% at nine metres, by 30% at 27 m, and not at all at 81 m. Inhibition by the MCH device varied with distance (m) from the source according to the function 0.79 − 0.092 x 0.51 ( R 2 = 0.986). Decline of attractant inhibition with distance from the MCH device was much less steep than would have been expected if catch inhibition had varied directly with the average airborne concentration of MCH.